Phosphoproteomic Alterations of Ionotropic Glutamate Receptors in the Hippocampus of the Ts65Dn Mouse Model of Down Syndrome - Gómez de Salazar, Macarena; Grau, Cristina; Ciruela, Francisco; Altafaj, Xavier (Frontiers in Molecular Neuroscience, 2018)
Down syndrome (DS), the main genetic cause of intellectual disability, is associated with an imbalance of excitatory/inhibitory neurotransmitter systems. In agreement with DS condition, the phenotypic assessment and pharmacotherapy interventions in DS murine models strongly pointed out glutamatergic neurotransmission alterations (specially affecting ionotropic glutamate receptors, iGluR) that might contribute to DS pathophysiology. Ionotropic glutamate receptors play a critical role in fast-mediated excitatory transmission, a process underlying synaptic plasticity. Biochemically, neuronal plasticity is modulated by post-translational modifications, allowing rapid and reversible adaptation of synaptic strength. Among these modifications, phosphorylation/dephosphorylation processes strongly dictate iGluRs protein-protein interactions, cell surface trafficking and subsynaptic mobility. Hence, we hypothesized that dysregulation of phosphorylation/ dephosphorylation balance might affect neuronal function, which in turn could contribute to the glutamatergic neurotransmitter alterations observed in DS. To address this point, we biochemically purified subsynaptic hippocampal fractions from adult Ts65Dn mice, a trisomic mouse model recapitulating DS phenotypic alterations. Proteomic analysis showed significant alterations of the molecular composition of subsynaptic compartments of hippocampal trisomic neurons. Further, we characterized iGluRs phosphopattern in the hippocampal glutamatergic synapse of trisomic mice. Phosphoenrichment-coupled Mass Spectrometry analysis revealed specific subsynaptic- and trisomy-associated iGluRs phosphorylation signature, concomitant with differential subsynaptic kinases and phosphatases composition of Ts65Dn hippocampal subsynaptic compartments. Furthermore, biochemical data were used to build-up a genotype-kinome-iGluRs phosphopattern matrix in the different subsynaptic compartments. Overall, our results provide a precise profile of iGluRs phosphopattern alterations in the glutamatergic synapse of the Ts65Dn mouse model, and support their contribution to DS-associated synaptopathy. The alteration of iGluRs phosphoresidues in Ts65Dn hippocampi, together with the kinases/phosphatases signature, identifies potential novel therapeutic targets for the treatment of glutamatergic dysfunctions in DS.